The Value of Central Corneal Thickness Measurements in Forensic Cases with Blunt Eye Injury - Isır, Aysun Baransel; Erbağcı, İbrahim; Saygılı, Oğuzhan; Özdil, Serdar; Okumuş, Seydi (The Bulletin of Legal Medicine, 2009)
In this study we aimed to determine forensic report process of blunt eye trauma cases and to determine central corneal thickness (CCT) value by ultrasonic pachymeter. We examined 76 cases with blunt eye trauma who were sent by public prosecutors to Gaziantep University Department of Forensic Medicine between 2004 and 2007. We measured central corneal thickness by ultrasonic pachymeter in these cases. We considered to classify trauma time and duration to medical examination, in two groups: group I is up to three months; group II is more than 3 months. These cases’ healthy eyes were accepted as control group. Besides descriptive information like sex, age and étiologie factors of the trauma of these cases, mean and standard deviations of variables were calculated. Statistical analysis and calculations were performed using SPSS 13.0. The differences in CCT mean values of trauma and healthy eyes between groups were examined with the student’s t test. A p value less than 0.05 was considered statistically significant. In the study 47 of 76 cases were male, 29 were female (mean age 34.8 (16-56)). The étiologie factors of the trauma in order of decreasing percentage were 59.2% beat, 18.4% traffic accident, 13.2% industrial accident, 9.2% crash-dropping accident. In group I (30 cases), the mean CCT value in the eyes without trauma was 545.2 + 10.18 fi; 565.9 + 22.4 fi in the eyes with trauma (p0.05). Because the mean CCT values are higher in the eyes with blunt trauma compared to normal eyes in group I we suggested that it is suitable to wait for at least three months for forensic reports.Key words: Blunt eye trauma, ultrasonic pachymeter, central corneal thickness
Keywords: blunt eye trauma; ultrasonic pachymeter; central corneal thickness